Strategi Pemerintah Desa Dalam Peningkatan Pendapatan Asli Desa Melalui Program Pengelolaan Air Bersih Di Desa Cikalong Kecamatan Cimaung Kabupaten Bandung - Ramadhan, Akbar (CV RIFAINSTITUT, 2022)
Most of the people in Cikalong Village currently have difficulty getting clean water. Because the majority of them do not have a personal water source and depend on water sources managed by the village. Village Original Income is closely related to the management of village assets owned. In Cikalong Village itself, village assets are one of the village's original sources of income, one of which is the clean water management program, which is currently under construction. This clean water management program includes springs, buildings and equipment to support clean water. This research is a qualitative research, using strategy theory from Bintoro Tjokroamidjojo with variable goal setting, policy formulation, and operationalization. The results of this study indicate that the purpose of the clean water management program is to improve community welfare in the health sector, to meet community needs for access to clean water, and to increase Village Original Income. Then in the formulation of the policy, Cikalong Village Regulation Number 5 of 2021 concerning Clean Water Management became the legal basis for running this program. The Village Regulation regulates all matters relating to the clean water program. Then for operationalization, after the implementation of the clean water management program, there have been no complaints from the public regarding access to clean water. For plans for other villages to use water managed by Cikalong Village, this is a long-term development plan for Cikalong Village. Because more and more people use water, there will also be an increase in Village Original Income